Immunomodulatory and Anticancer Effects of Fridericia chica Extract-Loaded Nanocapsules in Myeloid Leukemia - Alice de Freitas Gomes; Adriane Dâmares de Souza Jorge Batalha; Carlos Eduardo de Castro Alves; Renata Galvão de Azevedo; Jesus Rafael Rodriguez Amado; Tatiane Pereira de Souza; Hector Henrique Ferreira Koolen; Felipe Moura Araújo da Silva; Francisco Celio Maia Chaves; Serafim Florentino Neto; Antônio Luiz Boechat; Gemilson Soares Pontes (MDPI AG, 2024)
Nanocapsules provide selective delivery and increase the bioavailability of bioactive compounds. In this study, we examined the anticancer and immunomodulatory potential of Fridericia chica (crajiru) extract encapsulated in nanocapsules targeting myeloid leukemias. Nanocapsules containing crajiru (nanocapsules-CRJ) were prepared via interfacial polymer deposition and solvent displacement. Size and polydispersity were measured by dynamic light scattering. Biological assays were performed on leukemia cell lines HL60 and K562 and on non-cancerous Vero cells and human PBMC. The anticancer activity was evaluated using cytotoxicity and clonogenic assays, while the immunomodulatory activity was evaluated by measuring the levels of pro- and anti-inflammatory cytokines in PBMC supernatants treated with concentrations of nanocapsules-CRJ. Nanocapsules-CRJ exhibited significant cytotoxic activity against HL60 and K562 cells at concentrations ranging from 0.75 to 50 μg/mL, with the greatest reductions in cell viability observed at 50 μg/mL (p < 0.001 for HL60; p < 0.01 for K562), while not affecting non-cancerous Vero cells and human PBMCs. At concentrations of 25 μg/mL and 50 μg/mL, nanocapsules-CRJ reduced the formation of HL60 and K562 colonies by more than 90% (p < 0.0001). Additionally, at a concentration of 12 μg/mL, nanocapsules-CRJ induced the production of the cytokines IL-6 (p = 0.0002), IL-10 (p = 0.0005), IL-12 (p = 0.001), and TNF-α (p = 0.005), indicating their immunomodulatory potential. These findings suggest that nanocapsules-CRJ hold promise as a potential therapeutic agent with both cytotoxic and immunomodulatory properties.